Race, Ethnicity, and the American Criminal Justice System: The Perceptions and Experiences of West Indian Men. (October 2019) - Robertson, O. Nicholas; Adelman, Robert M.
Using in-depth interview data from 30 young Black men of West Indian background, we examine their experiences with and perceptions of the American criminal justice system. Their experiences lead these men to contend that the system, especially police authorities, do not differentiate between Blacks based on ethnicity and subsequently treat West Indians and African Americans in a similar manner, that is, race trumps ethnicity. These men discuss their concerns about stereotypes of minorities, especially as they are reflected in the media, as the primary reasons for their treatment. However, these men also provide nuanced accounts in which not all system actors engage in discriminatory behavior. These accounts rest on an immigrant lens regarding criminal justice, which may indicate a more favorable outlook compared to their native-born Black counterparts. Overall, though, the interview data suggest that a Black–White divide regarding such perceptions will persist in an era of substantial sociodemographic change.